Assessment of the ecotoxicity of urban estuarine sediment using benthic and pelagic copepod bioassays - Charry, Maria P.; Keesing, Vaughan; Costello, Mark; Tremblay, Louis A. (PeerJ, 2018)
Urban estuarine sediments are sinks to a range of contaminants of anthropogenic origin, and a key challenge is to characterize the risk of these compounds to receiving environments. In this study, the toxicity of urban estuarine sediments was tested using acute and chronic bioassays in the benthic harpacticoid Quinquelaophonte sp., and in the planktonic calanoid Gladioferens pectinatus, two New Zealand copepod species. The sediment samples from the estuary tributary sites significantly impacted reproduction in Quinquelaophonte sp. However, results from one of the estuary sites were not significantly different to those from the tributaries sites, suggesting that chemicals other than trace metals, polycyclic aromatic hydrocarbons and ammonia may be the causative stressors. Sediment elutriate samples had significant effects on reproductive endpoints in G. pectinatus, and on the induction of DNA damage in cells, as shown by the comet assay. The results indicate that sediment contamination at the Ahuriri Estuary has the potential to impact biological processes of benthic and pelagic organisms. The approach used provides a standardized methodology to assess the toxicity of estuarine sediments.
Keywords: New Zealand; Contaminants; Stormwater; Survival; Reproduction; Genotoxicity; Guideline threshold levels; Larval development; Estuary